Managing Insomnia: A Review of Pharmacological and Non-Pharmacological Approaches - Kłossowska, Martyna; Badziąg, Magdalena; Skonieczna, Karolina; Szulc, Paulina; Kurczoba, Laura; Wiciun, Olimpia; Kądziołka, Olga; Ordon, Kacper (Quality in Sport, 2025)
Introduction and Aim: Insomnia is one of the most common sleep disorders, affecting about 10% of the population. It poses a significant public health concern due to its association with increased risk of depression, hypertension, obesity, diabetes, substance abuse, and suicide. Given its impact on health and quality of life, effective treatment is essential. This review aims to present pharmacological and non-pharmacological treatment methods for insomnia with proven scientific efficacy. Materials and Methods: A literature review was conducted using PubMed and Google Scholar, focusing on studies published between 2000 and 2024. Keywords related to pharmacological and non-pharmacological treatments of insomnia were used, and the most relevant articles were selected. Brief Description of the State of Knowledge: Cognitive behavioral therapy for insomnia (CBT-I) is considered the first-line treatment. It provides short-term efficacy comparable to pharmacotherapy, with longer-lasting benefits and fewer side effects. Pharmacological treatments should be used when CBT-I is unavailable or insufficient. Benzodiazepines and non-benzodiazepine hypnotics may be effective short term but carry significant risks, especially in older adults. Newer agents, such as melatonin receptor agonists, low-dose doxepin, and orexin receptor antagonists, offer additional options with improved safety profiles. Conclusions: Effective management of insomnia requires an individualized approach. CBT-I remains the preferred option, with pharmacotherapy considered when necessary. Proper treatment improves patient well-being and reduces the broader social and economic consequences of untreated insomnia.